Long-Term Prognosis of Patients With Coexisting Obesity and Malnutrition After Acute Myocardial Infarction: A Cohort Study. Issue 4 (3rd March 2023) - Kong, Gwyneth; Zhang, Audrey; Chong, Bryan; Lim, Jieyu; Kannan, Shankar; Han Chin, Yip; Ng, Cheng Han; Lin, Chaoxing; Khoo, Chin Meng; Muthiah, Mark; Dalakoti, Mayank; Kristanto, William; et al.
Abstract : Background: The double burden of malnutrition, described as the coexistence of malnutrition and obesity, is a growing global health issue. This study examines the combined effects of obesity and malnutrition on patients with acute myocardial infarction (AMI). Methods: Patients presenting with AMI to a percutaneous coronary intervention-capable hospital in Singapore between January 2014 and March 2021 were retrospectively studied. Patients were stratified into the following: (1) nourished nonobese, (2) malnourished nonobese, (3) nourished obese, and (4) malnourished obese. Obesity and malnutrition were defined according to the World Health Organization definition (body mass index ≥27.5 kg/m 2 ) and Controlling Nutritional Status score, respectively. The primary outcome was all-cause mortality. The association between combined obesity and nutritional status with mortality was examined using Cox regression, adjusted for age, sex, AMI type, previous AMI, ejection fraction, and chronic kidney disease. Kaplan-Meier curves for all-cause mortality were constructed. Results: The study included 1829 AMI patients, of which 75.7% were male and mean age was 66 years. Over 75% of patients were malnourished. Majority were malnourished nonobese (57.7%), followed by malnourished obese (18.8%), nourished nonobese (16.9%), and nourished obese (6.6%). Malnourished nonobese had highest all-cause mortality (38.6%), followed by the malnourished obese (35.8%), nourished nonobese (21.4%), and nourished obese (9.9%, P <0.001). Kaplan-Meier curves demonstrated least favorable survival in malnourished nonobese group, followed by malnourished obese, nourished nonobese, and nourished obese. With nourished nonobese group as the reference, malnourished nonobese had higher all-cause mortality (hazard ratio, 1.46 [95% CI, 1.10–1.96], P =0.010), but only a nonsignificant increase in mortality was observed in the malnourished obese (hazard ratio, 1.31 [95% CI, 0.94–1.83], P =0.112). Conclusions: Among AMI patients, malnutrition is prevalent even in the obese. Compared to nourished patients, malnourished AMI patients have a more unfavorable prognosis especially in those with severe malnutrition regardless of obesity status, but long-term survival is the most favorable among nourished obese patients.